(3Md YbO GdJMUjds - (3HOQ GdOjf eMeO Hf CSYO GdeYQha HGdJSJQis; (3GdSQGL GdGQehj , eMehO Hf CHj HcQ Hf CMeO, SQGL GdOjf CHh GdKfGA,J (B682 (3g` s
(3ChdgG (B:s
(3hHYO jbhd GdEeGe eMeO Hf CSYO Gdjefi GdeYQha HGdJSJQi hbO fWb Gdfbd s
(3BNQgG (B:s
(3bGd GdEeGe EfeG LeYJ gPg GdhLhg EP CcKQ efGXQGJ GdReGf ai Gdabg s
(3hQO GdYfhGf GdCUdi ai cX (B/1615s
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B166 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B155s
Keywords: (3CUhd Gdabgs